Frequency of Sarcopenia in Elderly Patients with Distal Radius Fracture - Mir, Asad Bilal; Asim Niaz Naqvi; Rehan Saleem; Adnan Anwar; Mudassar Liaquat; Usman Shah Bukhari (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the frequency of sarcopenia among elderly patients presenting with distal radius fracture.Study design: analytical cross-sectional studyPlace and duration of study: Combined Military Hospital Rawalpindi from 02-09-2025 to 25-02-2026Methods: A total of 266 patients aged ≥60 years with radiologically confirmed distal radius fractures were included irrespective of mechanism of injury. The severity of sarcopenia was determined as the thigh muscle girth measured in the anteroposterior and lateral radiographs of the femurs using DICOM software. Data was analyzed through SPSS-27. Chi-square test were used, keeping p-value ≤0.05 as statistically significant.Results: The total number of patients included in this study was 266. The mean ± SD age of the patients was 68.4 ± 6.7 years. Sarcopenia was identified in 104 (39.1%) patients. FOOSH was the mechanism of injury in 181 (68.0%) cases. FOOSH was significantly more frequent among sarcopenic patients compared to non-sarcopenic patients (84.6% vs. 57.4%; p